The Quest for Pulsating M Dwarf Stars - Rodríguez-López, Cristina (Frontiers in Astronomy and Space Sciences, 2019)
Recent fully non-adiabatic theoretical studies of M dwarf models show that they have the potential to excite radial, and low-order, low-degree non-radial modes, as well as solar-like oscillations, due to models being completely convective or having large convective envelopes. The observational efforts aiming at discovering pulsating M dwarfs with photometric ground-based and space observations, and with high-precision spectroscopy are presented. With periods predicted in the 20~min to 3~h range and empirically estimated amplitudes of just a few $μ$mag or a few tens of cm\,s$^{-1}$, a clear detection of a pulsating M dwarf has not yet been achieved, and the race is still open. The precision attained by the latest-generation high-resolution spectrographs, of the order of cm\,s$^{-1}$, may be the key to unveil the, until today, elusive pulsations in M dwarf stars.